Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT. Pos Indonesia Cabang Kebonrojo Surabaya - Arina Manasikana; Mei Retno Adiwati (Universitas Batanghari Jambi, 2022)
This study aims to analyze the impact of work environment and work discipline to employees performance on Pos Indonesia, Co. Ltd Branch kebonrojo Surabaya. This research is quantitative. There are 2 variables are used, those are independent variables which Work Environment and Work Discipline and dependent variables which Employees Performance. there are population in this study as much 59 employees. Sampling technique useed saturated sample which the entire population is the research sample. The data collection method uses a questionnaire distributed to employees of service and distribution process division. Data analysis uses Structural Equation Modeling (SEM). The results of the study are: (1) Work Environment has positive and not significant effects to employees performance (2) work discipline has positive and significant effects to employees performance.